(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT Islamic jurisprudence, in various eras, is considered a manifestation of the nation’s interest in this purified law, the law of justice, mercy, and reform. The doctrines that were based on its established principles and established rules were schools of consideration, research, deduction, and weighting based on evidence derived from the Book of God Almighty and the Sunnah of His Messenger, may God bless him and grant him peace. And peace be upon them, and the correct consensus, clear analogy, presumptive evidence, or fundamental or jurisprudential rules based on them, and after God’s grace and facilitation, the choice fell on what is well-known in the Maliki school of thought in my two issues: the ruling on a woman leading women in prayer, and the ruling on the testimony of a slanderer before performing the prayer. The punishment for him and before repentance is an example of a comparative jurisprudential study. It was a humble attempt on my part to address one of the terms of preference according to the Malikis.